Socio-emotional Impact of Popular English Nursery Rhymes on Children - Ghildyal, Prachi (THE PRIMARY TEACHER, 2017)
The quality of the curriculum of a nation may be gauged by its relevance to the country’s sociocultural context. The early years are the most significant for a child’s overall development. Preschool education is the first stage of organised education. Therefore, the curriculum must aim at providing an emotionally supportive, culturally relevant, and interactive and friendly environment to young learners. This paper tries to sensitise schools, teachers and parents to be cautious about what they expose their children to. It also presents an analysis of English nursery rhymes, a type of content, usually, included in the preschool curriculum. It tries to study the socio-emotional impact of these nursery rhymes on the young minds